Conformationally rigid molecular and polymeric naphthalene-diimides containing C6H6N2 constitutional isomers. Issue 33 (5th July 2021) - Abbinante, Vincenzo Mirco; García-Espejo, Gonzalo; Calabrese, Gabriele; Milita, Silvia; Barba, Luisa; Marini, Diego; Pipitone, Candida; Giannici, Francesco; Guagliardi, Antonietta; Masciocchi, Norberto
Abstract : New molecular and polymeric NDI-based materials, containing constitutional isomers of aromatic amines, have been prepared as powders and thin films, studied by XRD and grazing-incidence diffraction methods, and compared to n -alkyl aliphatic congeners. Abstract : Organic thin films based on naphthalenediimides (NDIs) bearing alkyl substituents have shown interesting properties for application in OLEDs, thermoelectrics, solar cells, sensors and organic electronics. However, the polymorphic versatility attributed to the flexibility of alkyl chains remains a challenging issue, with detrimental implications on the performances. Aryl analogues containing C6 H6 N2 constitutional isomers are herein investigated as one of the possible way-out strategies. The synthesis of molecular and polymeric species is described, starting from naphthaleneteracarboxyldianhydride with isomeric aromatic amines and hydrazine. The materials are fully characterized by spectroscopy, thermal and structural X-ray diffraction methods, both as bulk powders and thin films, revealing a rich structural landscape. Depending on the stereochemistry of the branching aryls, the compounds show a variety of parallel stacking of the NDI cores, and high structural stability upon heating, up to 560 °C in the polymeric form. Thin films prepared by spin coating from organic solvent solutions and studied by grazing-incidence X-ray diffraction exhibit a high degree of crystallinity indicating the intrinsic tendency of these molecules to self-assemble in an ordered fashion without the need for any post-processing technique. In line with other NDI-based diimides, UV-vis spectroscopy indicates the optical band gaps falling in the visible region (2.87–3.02 eV). DFT calculations reveal a significant lowering of the frontier orbital energies of the hydrazido derivative. Beyond solution processing, the high thermal stability and the absence of polymorphic forms of these materials suggest that sublimation-based routes for films and device preparation can also be followed.